2006
DOI: 10.1111/j.1464-410x.2006.06270.x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent radical retropubic prostatectomy and Lichtenstein inguinal hernia repair through a single modified Pfannenstiel incision: a 3‐year experience

Abstract: inguinal canal through the same incision and performed a Lichtenstein mesh repair, through the inguinal canal and avoiding placing mesh within the pelvis. Patients were followed at 1 and 6 weeks, 3-monthly for 1 year and 6-monthly thereafter. All clinical variables were entered into a database and analysed. RESULTSIn all, 450 men underwent RRP; 44 (10%) had inguinal hernia and in all, 56 hernias were repaired (32 unilateral and 12 bilateral; 16 indirect, 22 direct, six both) The mean ( SD ) age of the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…По мнению многих зарубежных коллег, проведение одновременной радикальной позадилонной простат-эктомии с протезированием пахового канала из еди-ного модифицированного разреза по Пфанненштилю является эффективным и безопасным [5,21]. А. Б. Си-пенко и соавт.…”
Section: материалы и методыunclassified
See 1 more Smart Citation
“…По мнению многих зарубежных коллег, проведение одновременной радикальной позадилонной простат-эктомии с протезированием пахового канала из еди-ного модифицированного разреза по Пфанненштилю является эффективным и безопасным [5,21]. А. Б. Си-пенко и соавт.…”
Section: материалы и методыunclassified
“…Один из них -повышение внутрибрюшного давления, которое регистрируют при ДГПЖ или РПЖ [4,5]. Поэтому многие авторы считают, что при сочетании этих забо-леваний с вентральной или паховой грыжей необходи-мо проведение одномоментного оперативного вмеша-тельства [5][6][7][8][9]. Более 30 % пациентов с грыжей имеют различные признаки дисплазии соединительной ткани (ДСТ), что необходимо учитывать при выполнении оперативного вмешательства.…”
Section: Introductionunclassified
“…The concomitant repair of inguinal hernias during prostatectomy has been well described with reports of satisfactory outcomes in both open and laparoscopic RP [9,13,14]. However, as robotic-assisted laparoscopic radical prostatectomy (RALP) continues to grow in popularity across the globe, attention has turned to the management of inguinal hernias during this procedure.…”
Section: Introductionmentioning
confidence: 97%
“…This Y approach prevents any inadvertent entry into inguinal canal and also facilitates concurrent inguinal hernia repair through the same incision. 8,24 This modification also reduces the chance of ilio inguinal and ilio hypogastric nerve entrapment, which is a known complication of classical Pfannenstiel approach. 25 Salonia et al, 26 in a prospective randomized study, concluded that outcome after Pfannenstiel approach for a RRP was not significantly different from a vertical midline incision.…”
Section: Modified Pfannenstiel Approach M Manoharan Et Almentioning
confidence: 99%
“…There were no major complications and only one patient had recurrence of a hernia. 24 We also performed penile prosthesis insertion in two patients through the same incision.…”
Section: Modified Pfannenstiel Approach M Manoharan Et Almentioning
confidence: 99%